An investigation of knowledge management implementation strategies - Sunassee, Nakkiran N (Rhodes University, Faculty of Commerce, Department of Information Systems, 2003)
The world is experiencing an era which has been termed the "knowledge age" or the "knowledge economy" . In this new context, knowledge is the primary commodity, and knowledge flows are regarded as the most important factors in the economy. The management of knowledge flows within organisations has become a crucial activity because many of the activities of organisations and the broader economic and social life today are knowledge-driven. In recent years, this managerial activity has become known as Knowledge Management. Equally important are the associated Knowledge Management implementation strategies. Driven by a need expressed by the South African Motor Vehicle Industry for a knowledge management implementation strategy tailored to their needs, this research aimed to develop a knowledge management implementation strategy suited to the needs of this industry. Following an extensive literature survey and a study of the target industry using Duffy's Knowledge Benchmarking Questionnaire, a model of knowledge management implementation is proposed that is suited to the needs of the South African Motor Vehicle Industry. The model consists of three main interlinked components: Knowledge Management of the Organisation, People, and Infrastructure and Processes. Furthermore, the model recommends a holistic approach to managing knowledge. The critical success factors of the model were tested by means of a survey of industry opinions that validated certain aspects of the model and motivated for changes in others. Additionally, despite the focus of the model on the target industry, it is considered sufficiently appropriate for use by other organisations.
Keywords: Knowledge management; Strategic planning; Automobile industry and trade -- South Africa -- Management